Tocilizumab in Systemic Juvenile Idiopathic Arthritis: Response Differs by Disease Duration at Medication Initiation and by Phenotype of Disease - Yan, Xin; Tang, Wenjing; Zhang, Zhiyong; Zhang, Yu; Luo, Chong; Tang, Xuemei (Frontiers in Pediatrics, 2021)
Objective We performed a single-center retrospective study to determine the different efficacy of Tocilizumab (TCZ) in early and late stage and three phenotypic subgroups (monocyclic, polycyclic, and persistent) of Systemic juvenile idiopathic arthritis (sJIA). Methods Clinical and serological parameters of 77 sJIA patients treated by TCZ were collected from November 1, 2013 to May 1, 2019. Patients were grouped based on the duration (group A<6 months (n=41) and group B>6 months (n=36) and divided into three phenotypes：monocyclic(n=12)，polycyclic (n=14) and persistent (n=51) course. Results At baseline, group A had pronounced ESR and fever，less active arthritis than group B (p＜0.05). After 12 weeks of therapy , TCZ alleviated fever, ESR, CRP and sJADAS scores both in group A and group B(p>0.05), while the efficacy of TCZ in relieving active arthritis in group A was better than group B (p<0.05). After 1 year of TCZ therapy, it showed that patients with monocyclic phenotype had the highest clinical response rate (75%, odds ratio = 2.3, 95% CI: 16.6–25.7, p=0.00) , followed by the polycyclic (35.7%, odds ratio =2.2, 95% CI: 11–19.5, p=0.00) and the persistent course (27.5%). Conclusion TCZ can quickly relieve fever and inflammation, especially when patients have less active arthritis with shorter disease duration. The long-term efficacy of TCZ is related to the phenotypes, among which the monocyclic is the best, and the persistent is the worst.